Non-governmental organizations as the link between university and company: the case about the arrastart project (Research, Society and Development, 2020)
This article explore as partnership between an NGO and a private company can help boost social entrepreneurship, based on the use of digital technologies, in mass universities, focused on teaching low-income youth. It is justified by the worldwide movements related to the creation of startups within Brazilian universities, and the relevance of these for the generation of revenues, since practices that serve young people from the periphery. The theoretical contribution of this article is to assist the understanding of how the leverage process of startups in university environments takes place with the support of NGOs. Regarding the methodological aspects, an exploratory research, of a qualitative and descriptive nature, was carried out through a case study using documentary analysis, participant observation, interviews with NGO teachers and managers, based on semi-structured scripts, and a focus group with some students benefited by the program. The results revealed that the lack of transparency in the transmission of information, as well as the different understandings about the objectives to be achieved with the project, constitute barriers that must be considered in the initial phase of the project, given the possibility of its results having the opposite effect than expected.